2020
DOI: 10.1051/0004-6361/202038538
|View full text |Cite
|
Sign up to set email alerts
|

Umbral chromospheric fine structure and umbral flashes modelled as one: The corrugated umbra

Abstract: Context. The chromosphere of the umbra of sunspots features an assortment of dynamic fine structures that are poorly understood and often studied separately. Small-scale umbral brightenings (SSUBs), umbral microjets, spikes or short dynamic fibrils (SDFs), and umbral dark fibrils are found in any observation of the chromosphere with sufficient spatial resolution performed at the correct umbral flash stage and passband. Understanding these features means understanding the dynamics of the umbral chromosphere. Ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 80 publications
7
18
0
Order By: Relevance
“…Our model offers an alternative explanation, interpreting downflowing UFs as a natural feature of the global process of sunspot oscillations. This is also the recent interpretation of Henriques et al (2020), but here we show that such downflows are evidence of the standing-wave nature of these oscillations. Henriques et al (2017) reported strong downflowing atmospheres for UFs, with velocities up to 10 km s −1 , whereas our model produces downflowing UFs with velocities around 1 km s −1 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our model offers an alternative explanation, interpreting downflowing UFs as a natural feature of the global process of sunspot oscillations. This is also the recent interpretation of Henriques et al (2020), but here we show that such downflows are evidence of the standing-wave nature of these oscillations. Henriques et al (2017) reported strong downflowing atmospheres for UFs, with velocities up to 10 km s −1 , whereas our model produces downflowing UFs with velocities around 1 km s −1 .…”
Section: Discussionsupporting
confidence: 91%
“…The analysis is also challenged by the sudden variations in the atmosphere during the time required by Fabry-Perot spectrographs, such as the Interferometric BIdimensional Spectrometer (IBIS, Cavallini 2006) and the CRisp Imaging SpectroPolarimeter (CRISP, Scharmer et al 2008), to scan the line (Felipe et al 2018b). However, observations of smallscale umbral brightenings using a cadence of 14 s exhibit some indication of a temporal evolution consistent with that predicted by our modeling (Henriques et al 2020). Upcoming observations with the National Science Foundation's Daniel K. Inouye Solar Telescope (DKIST, Rimmele et al 2020) will provide the ideal data for studying the temporal variations of UFs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Even emission features are difficult to observe with spatial and temporal resolutions sufficient to distinguish the responsible physical mechanisms. For example, much of the spatial and temporal structuring of umbral micro-jets that was originally thought to be reconnection related (Bharti, Hirzberger, and Solanki, 2013;Nelson et al, 2017b) may instead be the signature of a shock/compression front forming in the corrugated sunspot atmosphere, with the time varying emission reflecting local density/velocity structures that enhance or delay the shock along a steepening compression front (Henriques et al, 2020). DKIST will enable spectropolarimetric measurements of such dim small-scale features with sufficient polarimetric sensitivity to constrain their physical properties.…”
Section: Active Region Evolution and Sunspot Fine Structurementioning
confidence: 99%